2016
DOI: 10.1093/deafed/enw076
|View full text |Cite
|
Sign up to set email alerts
|

Concern for Others: A Study on Empathy in Toddlers with Moderate Hearing Loss

Abstract: Empathy, the ability to feel the emotions of others and respond affectively to these emotions, is an important factor in the development of social competence. The purpose of this study was to examine empathy levels in toddlers with moderate hearing loss (MHL) compared to toddlers with no hearing loss (nHL), and to explore the relation between language ability and empathy. We focused on affective empathy and the precursors of cognitive empathy. A total of 23 toddlers with MHL and 21 toddlers with nHL participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 44 publications
0
11
1
1
Order By: Relevance
“…The findings concerning mental state language are also of interest because of the association with social-emotional development (Devine & Hughes, 2018;Drummond et al, 2014;Dunn et al, 1991;Meins, 2013;Peterson & Slaughter, 2003). Since children with MHL more often encounter social-emotional difficulties (Dirks et al, 2017;Laugen et al, 2016Laugen et al, , 2017Netten et al, 2015Netten et al, , 2017, early interventionists should guide parents in talking about beliefs, knowledge, desires, and emotions while interacting with their chilren.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings concerning mental state language are also of interest because of the association with social-emotional development (Devine & Hughes, 2018;Drummond et al, 2014;Dunn et al, 1991;Meins, 2013;Peterson & Slaughter, 2003). Since children with MHL more often encounter social-emotional difficulties (Dirks et al, 2017;Laugen et al, 2016Laugen et al, , 2017Netten et al, 2015Netten et al, , 2017, early interventionists should guide parents in talking about beliefs, knowledge, desires, and emotions while interacting with their chilren.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to this complex abstract language is not only beneficial for children's language development, but also for their social-emotional development. This is especially of interest in children with MHL since they encounter difficulties in their social-emotional development (Dirks et al, 2017;Laugen, Jacobsen, Rieffe, & Wichstrom, 2016Netten et al, 2015Netten et al, , 2017. Talking with children about their own and others' thoughts, desires, and feelings promotes their social-emotional development (Devine & Hughes, 2018;Drummond, Paul, Waugh, Hammond, & Brownell, 2014;Dunn, Brown, Slomkowski, Tesla, & Youngblade, 1991;Meins, 2013;Peterson & Slaughter, 2003).…”
Section: Parental Linguistic Inputmentioning
confidence: 99%
See 1 more Smart Citation
“…When different types of empathic skills were investigated separately, the results were mixed. The levels of affective empathy were not found to be different between children with and without hearing loss (Dirks et al, 2017 ; Netten et al, 2015 ). Yet, parent reports and self-reports indicated that children with hearing loss showed fewer prosocial actions (Dirks et al, 2017 ; Netten et al, 2015 ) while looking more often at the person experiencing an emotion than TH children during an observational task (Netten et al, 2015 ).…”
mentioning
confidence: 99%
“…The levels of affective empathy were not found to be different between children with and without hearing loss (Dirks et al, 2017 ; Netten et al, 2015 ). Yet, parent reports and self-reports indicated that children with hearing loss showed fewer prosocial actions (Dirks et al, 2017 ; Netten et al, 2015 ) while looking more often at the person experiencing an emotion than TH children during an observational task (Netten et al, 2015 ). Preschoolers with a CI also exhibited difficulties in acknowledging others’ emotion expressions (Wang et al, 2019 ; Wang et al, 2016 ).…”
mentioning
confidence: 99%